Satellite-based investigation on the surface cooling effects of urban parks and their range – a case study for North Rhine-Westphalia, Germany - Krelaus, Leonie; Apfel, Joy; Rienow, Andreas (ERDKUNDE, 2021)
Green infrastructure (GI) has a cooling effect owing to shading and evapotranspiration and therefore has a climate regulating function within metropolitan areas. Urban parks are a type of GI that act as park cool islands (PCIs) and play a major role in mitigating the surface urban heat island. This study aims to (1) investigate the status quo of the surface cooling effect intensity of selected urban parks in North Rhine-Westphalia (NRW), including their cooling range, and to (2) propose a methodological approach for investigating the PCI intensity using remote sensing data considering the occurrence of mixed pixels. To achieve these tasks, land surface temperature values based on Landsat 8 images from three different days in 2018 and 2019 were observed. In addition, a method for the reduction of mixed pixels was developed. The results confirm a surface cooling effect of 1–5 K and thus the existence of a PCI. The impact of the surface cooling effect was found within a minimum range of 150 m. However, the process of identifying the cooling area was complicated by the high proportion of GI in cities in NRW, compared to other study areas. Further research on the influencing parameters of the surface cooling effect is needed.